Cyber bullying, traditional bullying and depression - Guðrún Inga Baldursdóttir 1987- (2013)
With increased technological evolution and availability of the Internet, a new form of bullying has developed called cyber bullying. The hypothesis is that victims of cyber bullying show more symptoms of depression than victims of traditional bullying. Participants in this research were from a random sample of 2000 children drawn from a population study carried out by The Icelandic Centre for Social Research (ICSRA). The participants were in grades five through seven in primary school in Iceland. The data were collected with administration of a questionnaire. The independent variables were gender, victim of cyber bullying, victim of traditional bullying and traditional bully. The dependent variable was depression. The prevalence of cyber bullying was between 0.5% and 1.4% and for traditional bullying it was between 1.5% and 3.6%. The hypothesis was not supported, even though being a victim of cyber bullying had shared variability with depression of 10.2% it was not more than the shared variability of victim of traditional bullying and depression (14.0%). These results indicate that being a victim of cyber bullying has psychological impact though less than for a victim of traditional bullying. Með aukinni tækniþróun og aðgengi að veraldarvefnum hefur myndast nýtt form eineltis kallað neteinelti. Kenningin er að fórnarlömb neteineltis sýni meiri þunglyndiseinkenni en fórnarlömb hefðbundins eineltis. Þátttakendur í þessari rannsókn eru úr tilviljunarkenndu úrtaki 2000 barna tekin út úr þýðisrannsókn framkvæmd af Rannsóknum og greiningu. Þátttakendur voru í fimmta til sjöunda Bekk í grunnskóla í Íslandi. Gögnum var safnað með notkun spurningalista. Óháðu breyturnar voru kyn, fórnarlamb neteineltis, fórnarlamb hefðbundins eineltis og hefðbundinn gerandi. Háð breyta var þunglyndi. Algengi neteineltis var 0.5% til 1.4% og fyrir hefðbundið einelti var algengi 1.5% til 3.6%. Kenningin var ekki studd, en jafnvel þó að þolendur neteineltis hafi sýnt 10.2% sameiginlegt frávik þunglyndis, var það minna en sameiginlegt ...